Impact of Pirfenidone on Patient-Reported Outcomes in Patients With Idiopathic Pulmonary Fibrosis From the Pulmonary Fibrosis Foundation Patient RegistryTake-home Points - Mohleen Kang, MD, MS; Sachin Gupta, MD; Yi-Hsuan Tu, PhD; Karina Raimundo, MS; Anisha M. Patel, PhD; Kevin R. Flaherty, MD (CHEST Pulmonary)
Background: Patients with idiopathic pulmonary fibrosis (IPF) experience debilitating symptoms. Although antifibrotics may slow lung function decline, their impact on patients’ health-related quality of life and disease symptoms in the real world remains unknown. Research Question: What is the impact of pirfenidone vs no treatment on health-related quality of life and IPF-related symptoms of cough, dyspnea, and fatigue? Study Design and Methods: This retrospective analysis included patients with IPF aged ≥ 55 years enrolled in the Pulmonary Fibrosis Foundation Patient Registry between March 2016 and December 2021. Change from baseline in patient-reported outcome measures (PROMs), including the Leicester Cough Questionnaire, University of California, San Diego Shortness of Breath Questionnaire (UCSD SOBQ), Fatigue Severity Scale, and Short-Form 6-Dimension questionnaire were assessed at months 6, 12, and 18 in patients receiving pirfenidone vs no treatment. A marginal structure model accounted for time-varying confounding caused by FVC % predicted and diffusing capacity of the lungs for carbon monoxide % predicted. Results: In the Leicester Cough Questionnaire population (n = 237; pirfenidone, n = 155; no treatment, n = 82), treatment groups differed in age, insurance, and FVC % predicted. In the unadjusted analyses, mean changes in PROMs differed numerically between treatment groups; however, based on the marginal structure model, no significant differences were found in adjusted mean changes in PROMs. When analyzed by Gender, Age, and Physiology score, a clinically meaningful reduction in worsening of pirfenidone vs no treatment was observed in the adjusted mean change of UCSD SOBQ score at month 12 in patients with Gender, Age, and Physiology score stage 2/3. Interpretation: Similar to previous findings, the difference in UCSD SOBQ scores observed in this real-world analysis suggests that patients with more advanced IPF may experience less dyspnea when receiving pirfenidone vs no treatment. Further research is needed to confirm this finding. Trial Registry: ClinicalTrials.gov; No.: NCT02758808; URL: www.clinicaltrials.gov